Stochastic fluctuations and distributed control of gene expression impact cellular memory. - Guillaume Corre; Daniel Stockholm; Ophélie Arnaud; Gaël Kaneko; José Viñuelas; Yoshiaki Yamagata; Thi My Anh Neildez-Nguyen; Jean-Jacques Kupiec; Guillaume Beslon; Olivier Gandrillon; András Paldi (PLoS ONE)
Despite the stochastic noise that characterizes all cellular processes the cells are able to maintain and transmit to their daughter cells the stable level of gene expression. In order to better understand this phenomenon, we investigated the temporal dynamics of gene expression variation using a double reporter gene model. We compared cell clones with transgenes coding for highly stable mRNA and fluorescent proteins with clones expressing destabilized mRNA-s and proteins. Both types of clones displayed strong heterogeneity of reporter gene expression levels. However, cells expressing stable gene products produced daughter cells with similar level of reporter proteins, while in cell clones with short mRNA and protein half-lives the epigenetic memory of the gene expression level was completely suppressed. Computer simulations also confirmed the role of mRNA and protein stability in the conservation of constant gene expression levels over several cell generations. These data indicate that the conservation of a stable phenotype in a cellular lineage may largely depend on the slow turnover of mRNA-s and proteins.